Design of Mass Burial Sites for Safe and Dignified Disposal of Pandemic Fatalities. Issue 8 (24th November 2020) - Leong, Eng-Choon; Aboel-Naga, Hossam; Goli, Venkata Siva Naga Sai; Jha, Bhagwanjee; Pathak, Pankaj; Singh, Devendra Narain
Abstract : The huge number of fatalities due to COVID-19 pandemic has imposed an unprecedented pressure on existing burial facilities. Thus, mass burial is being used in different parts of the world to cope with this unusual situation. As a dead body might be contagious at least for hours, if not days, there is a need to manage/design/construct the mass burial considering the safe handling of coffins and other environmental, social, economical, and ethical/ dignity aspects. However, the guidelines of World Health Organization (WHO) do not thoroughly address the potential risk associated with groundwater pollution due to mass burial construction. Hence, the present study discusses the potential risk of groundwater pollution in the mass burial sites and sheds light on the factors that control the survival/retention of bacteria and viruses in porous media. Furthermore, using the available knowledge on designing/monitoring municipal/industrial waste disposal sites, cost-effective and simple construction method of mass burial is proposed to mitigate its potential environmental impact.